(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
During the Hindu festival of Janmashtami, many people fast and consume buckwheat flour (kuttu ka atta) as a gluten-free substitute. However, incidents of buckwheat poisoning have surfaced, raising concerns regarding its safety during fasting. This study aimed to investigate the clinical and epidemiological characteristics, identify predictors of severity, evaluate biochemical markers, and examine the medicolegal implications of buckwheat poisoning associated with Janmashtami fasting. A retrospective review was conducted of 110 patients admitted with suspected buckwheat poisoning at a tertiary care teaching hospital. Data on demographics, clinical symptoms, severity factors, and biochemical parameters were collected, followed by analysis. The study also explored medicolegal dimensions to understand the broader impact of these poisoning cases. The findings revealed that most patients were adult males from lower socioeconomic groups. The most common symptoms observed were gastrointestinal issues, respiratory problems, and neurological disturbances. Factors predicting the severity of poisoning were identified, including the amount of buckwheat consumed, existing health conditions, and delays in seeking medical care. Biochemical analysis revealed elevated levels of markers corresponding to the severity of symptoms. Medicolegal analysis pointed to shortcomings in food safety regulations, labelling, and public awareness, suggesting potential legal liabilities for food vendors and producers. Buckwheat poisoning during Janmashtami fasting presents a notable health risk, necessitating public health measures and stricter food safety standards. Healthcare providers should be particularly alert during fasting periods, and public awareness campaigns are essential to prevent future cases. Medicolegal considerations highlight the need for robust food safety legislation and improved consumer education to safeguard the public health.